Pengaruh PjBL-STEAM (Science, Technology, Engineering, Art, and Math) Terhadap Ketahanan Fokus (Attention Span) Anak Usia Dini dalam Kegiatan Eksperimen Sains Sederhana - Samsu Nurfalah; Lelis Nuramalia; Ida Laelasari; Siti Aisyah (PT. Nawa Edukasi Nusantara, 2026)
This study was motivated by the limited attention span of young children in science learning activities that require attention, active engagement, and the ability to follow learning stages until completion. Teacher-centered learning and limited hands-on experiences often make children easily distracted during classroom activities. This study aimed to examine the effect of the PjBL-STEAM model on early childhood attention span in simple science experiments. This research used a quantitative approach with a pre-experimental one-group pretest-posttest design. The subjects were 15 group B children aged 5 to 6 years at PAUD Ar Rasyid. Data were collected using an observation sheet consisting of eight indicators of attention span and were analyzed through descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed Rank Test. The findings showed that the mean pretest score was 23.53, while the mean posttest score was 23.00. The difference score was not normally distributed, with a significance value of 0.034. The Wilcoxon test obtained a Z value of -2.126 and an Asymp. Sig. value of 0.033. These results indicate that the PjBL-STEAM model had a significant effect on changes in early childhood attention span, although the direction of change did not show improvement. This study highlights the need to implement PjBL-STEAM gradually, simply, and structurally so that science experiments can support children in maintaining attention during learning activities.